Community-Based Springs Management of The Sukolilo Karst Landscape Area to Fulfill Clean Water Needs - Ervando Tommy, Al-Hanif; Dewi Liesnoor Setyowati; Puji Hardati; Jamhur; Ray Gerraldo, S Tambunan; Figo Dwi Akbar (GEOGRAFI, 2025)
The demographic growth rate development is in line with economic dynamics that drive environmental degradation. This occurrence is evident within the KBAK Sukolilo area, which has evolved into a cultivation area despite being designated as a geological cultural heritage site by the Ministry of Energy and Mineral Resources since 2014. The primary issue in the Purwodadi region is the annual occurrence of drought. Ninety-seven villages across 14 districts in Grobogan experience a clean water crisis. The research objectives are: 1) mapping land use distribution and potential water sources in KBAK Sukolilo and 2) analyzing water management for meeting water needs. The research object is the springs located in KBAK Sukolilo, Grobogan District, covering six districts. The research method involves surveying data collection on the potential and quality of springs in KBAK Sukolilo, conducting interviews, and utilizing descriptive analysis and geospatial information analysis techniques. The research findings indicate a dynamic change in land use, with Plantations (22.5%), Fields (13.7%), Settlements (9.4%), Irrigated Rice Fields (34.8%), Rain-fed Rice Fields (12.3%), Bushes (6.9%), and Empty Land (0.4%). The karst area of KBAK Sukolilo, which plays a crucial hydrological role, boasts 28 springs, with the highest potential at the Ngakiman spring, with a discharge of 146.5 liters per second, and the lowest potential of 2 liters per second found in 8 springs in the Sukolilo Karst area in Grobogan.